Autophagy and Cancer - Wang, Hong-Gang (Current Cancer Research,, 2013)
This book covers the latest advances in the field of autophagy and cancer from the basics of the molecular machinery for autophagy induction and regulation up to current areas of interest, including modulation of autophagy and drug discovery for cancer prevention and treatment. The reader will be initially introduced to the historical context of autophagy, followed by a summary of the key players in autophagy, a discussion on the origin of autophagosomes, and an overview of signal transduction regulation of autophagy. The next chapters deal with the complex relationship between autophagy and tumorigenesis through in-depth discussions of how autophagy influences cell survival, apoptosis, inflammation, immunity, tumor microenvironment, metabolic stress, DNA damage, and genomic instability. The remaining chapters discuss how autophagy affects cancer cell response to therapy and how to best modulate autophagy for therapeutic benefit - what to target and how to target. We hope that this monograph will be an invaluable reference source for professionals, students, postdoctoral fellows, and senior scientists working in the fields of autophagy and cancer.